Soft morphing hand driven by SMA tendon wire. (15th November 2016) - Kim, Hyung-Il; Han, Min-Woo; Song, Sung-Hyuk; Ahn, Sung-Hoon
Abstract: Most existing approaches to developing robotic manipulators or artificial hands have used rigid components, with joints, linkages, gears, and motors. Rigid robotic systems can perform tasks with precise and articulated motion, but require complex integrated feedback-based control systems. Soft robotics is an emerging research field that uses deformable materials to build systems that are compliant and adaptable via simple integrated mechanisms, enabling biomimetic behavior with compact systems. Here, we report a novel tendon-driven bending actuator using smart soft composite (SSC) and shape memory alloy (SMA). First, an artificial finger was designed based on a SMA wire and a sliding mechanism, which mimics flexion of the human hand. This artificial finger has a soft hinge structure to enable the bending motion of the actuator. Experiments were conducted to evaluate the bending and load resistance of the artificial finger, and an optimal material composition was identified. The bending performance of the actuator was measured with various numbers of glass fiber sheets, and two-layered actuator showed the best performance in terms of the trade-off relationship between the bending capacity and the load holding capacity – bending angle of 305° with weight of 20 g and bending angle of 61° with weight of 60 g. Finally, a prototype robotic hand was then developed using four tendon-driven SSC fingers and a thumb, and grasping capabilities were demonstrated with various objects with diverse shapes.